PENGARUH PENERAPAN SMART GOVERNANCE TERHADAP PENINGKATAN KUALITAS LAYANAN ADUAN MASYARAKAT PEMERINTAH PROVINSI DKI JAKARTA: Studi Kasus Pada Sistem Cepat Respon Masyarakat (CRM) - Muhamad Satria Ardiansyah (2023)
This thesis aims to discuss the effect of the presence of Smart Governance on the quality of complaint services belonging to the Provincial Government of DKI Jakarta by using the New Public Service theory from Denhardt & Denhardt. The method used is descriptive quantitative method using primary data sources and secondary data. The sampling technique was carried out using Accidental Sampling. Researchers used 6 stages of testing namely Validity Test, Reliability, Correlation, Simple Linear Regression, Coefficient of Determination, and Hypothesis. The final results of this study indicate that there is a positive and significant influence from the implementation of Smart Governance, especially a complaint service called CRM on improving the quality of complaint services for the Provincial Government of DKI Jakarta. The two variables studied have 0.610 correlation which is belong to a strong correlation. Then based on the results of the test for the coefficient of determination, a figure of 43.2% is obtained, which means that the X variable in this study, namely the implementation of Smart Governance contributes 43.2% to the Y variable, namely improving the quality of service complaints from the Provincial Government of DKI Jakarta, while the other 56.8% is influenced by other factors not examined in this study. Based on the results of the hypothesis test, H0 is rejected and H1 is accepted because there is positive and significant influence from the Implementation of Smart Governance on Improving the Quality of Service Complaints of the Provincial Government of DKI Jakarta.